Induced Mutation in Rice by Tissue Culture I - P. Pongtongkam; P. Ratisoontorn; S. Suputitada; S. Peyachoknagul; L. Ngernsiri; B. Silayoi; P. Rodrangboon; K. Klakhaeng; R. Senghaphan (Agriculture and Natural Resources, 1994)
Seeds of Basmati 370 rice variety were cultured on the modified MS medium supplemented with various concentrations of 2,4-D, NAA and kinetin. The suitable callus induction medium was the modified MS medium containign I mg/l 2,4-D, 2 mg/l NAA and 1 mg/l kinetin. Calli from this medium were divided into two groups, one was 3 week old calli (non subcultured calli) and the other was 6 week old calli (subcultured calli). Both groups seemed to grow and develop into plantles quite well on the modified MS medium supplemented with 2 mg/l kinetin. However the percentage of plantles induction from 3 week old calli was better. Calli of both groups were irradiated with different doses of gamma radiation and were cultured on the regenerated medium. The 3 week old calli were better than 6 week old calli in regenerating into plantles.